Qualidade hospedeira e temperatura na biologia de Diaeretiella rapae (McIntosh, 1855) (Hymenoptera: Braconidae, Aphidiinae) - Souza, Monique Ferreira de (2014)
Survival, development time, fertility, behavior, longevity, and other biological features of Diaeretiella rapae (McIntosh) are conditioned by temperature and host. However, studies of host quality changes due to its temperature adaptability have not been performed yet. Therefore, this study evaluated the adaptability of Lipaphis pseudobrassicae (Davis) and Myzus persicae (Sulzer) to high temperature and its effect on the quality of these aphids as hosts and on the thermal threshold of D. rapae. The biology of the aphids was compared at 19 and 28°C, using 60 replicates per temperature, to determine the adaptability of the host to temperature. Changes in host quality as a function of different temperatures were determined by maintaining a female of D. rapae for one hour in a Petri dish containing thirty 2nd instar nymphs of one host species for oviposition. The plates containing the parasitized aphids were transferred to 16, 19, 22, 25, 28 or 31°C to evaluate the biological features of the parasitoid and the hind tibia length of the mummy and females of D. rapae, using 10 replicates per host and temperature. Thermal threshold of D. rapae was determined using the development time data. No differences in the biological features of L. pseudobrassicae and M. persicae were observed at 19°C. Reproductive period and longevity of aphids also did not differ at 28°C; however, development time, rate of immature survival and total fecundity rates were greater in L. pseudobrassicae than in M. persicae. Also, the percentage of emergence and total viability rate of D. rapae were greater in L. pseudobrassicae. The development time of D. rapae in L. pseudobrassicae was shorter than in M. persicae at 28 and 31°C for females and at 31 °C for males. The thermal threshold of D. rapae was 6.38 and 3.33°C for females and 4.45 and 3.63ºC for males developed on L. pseudobrassicae and M. persicae, respectively. The hind tibia length of mummified M. persicae was greater than in L. pseudobrassicae at all temperatures. The hind tibia length of the parasitoid was greater at 25 and 28°C when reared on L. pseudobrassicae than on M. persicae. The host L. pseudobrassicae showed better adaptation than M. persicae to elevated temperatures, which resulted in better quality as host for D. rapae at temperatures of 28 and 31°C and higher base temperature when the parasitoid developed in the L. pseudobrassicae than in M. persicae. The adaptation of the host to high temperatures is determinant for the host quality for the parasitoid in that same climatic condition.